Portion size and consistency as indicators of complementary food energy intake - Emily C. Faerber; Aryeh D. Stein; Amy Webb Girard (Wiley, 2021)
Abstract We evaluated whether novel portion size and consistency indicators can identify children with low complementary food energy intake in southern Ethiopia. We conducted 24‐h dietary recalls with caregivers of 548 children aged 6-13 months; additionally, caregivers estimated their child's usual portion size using uncooked rice and selected which of five photographs of porridges of varying consistencies most closely matched the food their child usually ate. Complementary food energy and density from the 24‐h recall were used as reference values. We computed correlation coefficients and areas under receiver operating characteristic curves (AUC) and conducted sensitivity and specificity analyses to classify children with low complementary food energy intake. The median complementary food energy intakes for children 6-8, 9-11 and 12-13 months were 312, 322 and 375 kcal; median estimated portion sizes were 50, 58 and 64 ml, respectively. Estimated portion size correlated with total complementary food energy intake and with average energy and quantity consumed per feeding (r = 0.42, 0.46 and 0.45, respectively, all p < 0.001). Reported food consistency was weakly correlated with total complementary food energy intake (r = 0.18) and density (r = 0.10), and energy density of porridge only (r = 0.24, all p < 0.05). Predicted energy intake combining feeding frequency and portion size predicted inadequate energy intake better than did feeding frequency alone in infants 6-8 months [∆AUC = 0.16, 95% confidence interval (CI) 0.04, 0.28] and 9-11 months (∆AUC = 0.09, 95% CI 0.04, 0.14). Caregiver estimates of portion size can improve identification of infants with low complementary food energy intake when more robust dietary assessment is not feasible.